Long-term Potentiation at Spinal C-fiber Synapses: A Target for Pathological Pain - Liu, Xian-Guo; Zhou, Li-Jun (Current Pharmaceutical Design, 2015)
Long-term potentiation (LTP), referring to a lasting increase in efficacy of synaptic transmission, is a common mechanism of memory storage in central nervous system (CNS). LTP at C-fiber synapses in spinal dorsal horn is considered as a synaptic model of pathological pain, as the spinal LTP is only induced by noxious electrical and natural stimuli but not by innoxious ones and LTPinducible stimulation is capable of leading to lasting behavioral signs of pathological pain in human and in animals. The molecular mechanisms of spinal LTP at C-fiber synapses are similar to hippocampal LTP in following aspects. Induction of LTP depends on postsynaptic Ca2+ rise resulting from opening of N-methyl-D-aspartate channels (NMDA) and voltage-gated calcium channels (VGCCs), and Ca2+ release from intracellular store; Early-phase LTP (<3h) needs activation of intracellular protein kinase A (PKA), protein kinase C (PKC), calcium/calmodulin-dependent protein kinase II (CaMKII), phospholipase C (PLC) and release of nitric oxide (NO); Late-phase LTP (>3h) is dependent on de novo protein synthesis; Activation of either dopamine D1 receptors or PKA, and extrogenous brain-derived neurotrophic factor (BDNF) or ATP directly induces late-phase LTP. Therefore, the drugs targeting at the above molecules may impair memory function of hippocampus. The striking difference between hippocampal LTP and spinal LTP at C-fiber synapses is that activation of glial cells and the over–expression of proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α) and interleukin– beta (IL-1β), inhibit LTP in hippocampus, but promote LTP in spinal dorsal horn. The drugs targeting at the neuroinflammatory process may not only attenuate pathological pain but also improve memory in hippocampus.
Keywords: pathological pain